Monetary policy rules for managing aid surges in Africa - Christopher Adam; Edward Buffie; Stephen O'Connell; Catherine Pattillo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
We examine the properties of alternative monetary policy rules in response to large aid surges in low-income countries characterized by incomplete capital market integration and currency substitution. Using a dynamic stochastic general equilibrium model, we show that simple monetary rules that stabilize the path of expected future seigniorage for a given aid flow have attractive properties relative to a range of conventional alternatives, including those involving heavy reliance on bond sterilization or a commitment to a pure exchange rate float. These simple rules, which are shown to be robust across a range of fiscal responses to aid inflows, appear to be consistent with actual responses to recent aid surges in a range of post-stabilization countries in Sub-Saharan Africa.
Keywords: O23; E52; F31; F35; 330; monetary policy; currency substitution; aid; Africa; DSGE models; Geldpolitik; Entwicklungshilfe; Dynamisches Gleichgewicht; Afrika